Qualitative and quantitative determination of chemical constituents in Jinbei oral liquid, a modern Chinese medicine for coronavirus disease 2019, by ultra-performance liquid chromatography coupled with mass spectrometry - Zhang, Aijun; Xu, Qingcui; Jiang, Juanjuan; Zhao, Zimo; Zhang, Liangzong; Tao, Kai; Cao, Guiyun; Zhang, Jinghua; Ding, Lin; Meng, Zhaoqing; Dong, Wenyao; Wang, Chunxia (Frontiers in Chemistry, 2023)
Traditional Chinese medicine (TCM) has the advantages of syndrome differentiation and rapid determination of etiology, and a large number of traditional Chinese medicine prescriptions have been applied to the clinical treatment of corona virus disease 2019 (COVID-19)COVID-19. Among them, Jinbei Oral Liquid (JBOL) has also shown obvious curative effect in clinic, but the related material basic research is relatively limited. Therefore, in this process, a systematic data acquisition and mining strategy was established using ultra high performance liquid chromatography coupled with quadruple time of flight mass spectrometry (UPLC-Q-TOF-MS). With the optimized conditions, a total of 118 peaks were tentatively characterized, including 43 flavonoids, 26 phenylpropanoids, 14 glycosides, 9 phthalides, 8 alkaloids and others. Subsequently, in order to determine the content of relevant pharmacological ingredients, we firstly exploited the ultra high-performance liquid chromatography method coupled with triple-quadrupole tandem mass spectrometry (UPLC-QqQ-MS/MS) method for simultaneous detection of 31 active ingredients within 17 minutes, and the validation of methodology showed that this method has good precision and accuracy. Moreover, in combination with the pharmacology of single medicinal material, the quantitative 31 compound ingredients preliminarily confirmed the efficacy of JBOL and which laid a foundation for its in-depth study of network pharmacology.